The Role of Diplomatic and Consular Relations in Handling the Siti Aisyah Case - Dethan, Larissa Doraltina (Universitas Sebelas Maret, 2023)
Indonesia and Malaysia are two neighboring countries that also have a relationship that always experiences ups and downs but also maintains a fairly strong brotherly relationship because it is influenced by several similarities such as culture, politics and ideology. But apart from that, Indonesia and Malaysia must also have experienced conflicts that made relations between the two countries tenuous. One of them is regarding the case of Indonesian citizens in Malaysia who were charged by the Malaysian government with killing Kim Jong Nam, who is the half brother of North Korean President, Kim Jong Un. So to overcome this problem, Indonesia needs to carry out diplomacy through diplomatic and consular relations with Malaysia, so that problems can be resolved properly based on mutual agreement. In this study, the authors aim to analyze the diplomatic and consular roles of Indonesia in handling the case. The methodology used in this study is a qualitative methodology through primary and secondary data collection. So that in the end, Siti Aisyah, who became the defendant, was acquitted because it was proven that she did not kill Kim Jong Nam.